2006
DOI: 10.3354/meps328183
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasitic sea lice (Lepeophtheirus salmonis and Caligus elongatus) infestations of wild, adult, one sea-winter Atlantic salmon Salmo salar returning to Scotland

Abstract: Caligid ectoparasitic copepods are major pathological pests on cultured Atlantic salmon Salmo salar L., and their population biology has been well studied in the farm environment. The ecology of caligid infestations of wild salmon is, by contrast, rather poorly understood. We monitored return migrant one sea-winter wild Atlantic salmon in Scotland annually for infestations of 2 caligids, Lepeophtheirus salmonis (Krøyer) (between 1998 and 2005) and Caligus elongatus Nordmann (between 1999 and2005). Prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Burdens of 20+ adult Lepeoph theirus salmonis fish -1 on wild adult Atlantic salmon (Todd et al 2006) and sea trout (Urquhart et al 2008) have been recorded with no obvious detri- lice (all stages) abundance on the sentinel fish and on the fish from 2 farms using both untransformed and de-trended data. The cross-correlation at lag zero is the correlation between counts in the sentinel cages and the farms in the same month; the cross-correlation at a lag of 1 mo is the correlation between counts in the sentinel cages and the farms 1 mo before; and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Burdens of 20+ adult Lepeoph theirus salmonis fish -1 on wild adult Atlantic salmon (Todd et al 2006) and sea trout (Urquhart et al 2008) have been recorded with no obvious detri- lice (all stages) abundance on the sentinel fish and on the fish from 2 farms using both untransformed and de-trended data. The cross-correlation at lag zero is the correlation between counts in the sentinel cages and the farms in the same month; the cross-correlation at a lag of 1 mo is the correlation between counts in the sentinel cages and the farms 1 mo before; and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Plankton sampling discovered higher densities of L. salmonis copepodites in very shallow water along the seashore and in estuarine areas of Ireland and Scotland (Costelloe et al 1995(Costelloe et al , 1998McKibben & Hay 2004). While the same copepodite distribution may be expected in British Columbia, it requires confirmation because the Pacific and Atlantic populations of L. salmonis are genetically distinct (Tjensvoll et al 2006;Todd et al 2006) and may have different evolutionary adaptations. Thus, at least in Europe, empirical data indicated that the infective copepodites of L. salmonis concentrated in the path of migrating salmonids in estuaries.…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
“…However, Todd et al (2006) found that wild Atlantic salmon in poor condition were not more likely to have high lice burdens. At low density (less than three lice per fish or less than 0.65 lice g 21 fish), lice had no effect on the condition of juvenile pink salmon (Butterworth et al 2008).…”
Section: Research Progress (A) Larval Dispersal and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Timeseries data from more than seven years have been collected for L. salmonis and C. elongatus abundances on wild salmon captured in coastal bag nets in marine waters off the north coast of Scotland (Todd et al, 2006). The fish remained live and free-swimming in these traps and thus the data were more reliable.…”
mentioning
confidence: 99%